Dominant factors and food waste reduction strategies in hospitals: A systematic literature review - Afrizal Afrizal; Fajar Ari Nugroho; Irma Sarita Rahmawati; Tita Septi Handayani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Food waste in hospitals is a critical issue because of its economic, environmental, and nutritional service implications. Previous studies have reported inconsistent findings regarding the dominant factors influencing food waste, particularly those related to food quality, patient characteristics, and the delivery of services. This study aimed to identify the dominant determinants of hospital food waste and analyze strategies for reducing it. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The review included 30 national and international articles published between 2020 and 2025, retrieved from Scopus and ScienceDirect based on pre-defined inclusion and exclusion criteria. The findings indicate that hospital food waste is a multifactorial phenomenon influenced by internal and external factors. Food quality, particularly taste and appearance, emerged as the most frequently reported determinant, followed by patient-related factors such as appetite and clinical condition and service-related factors including staff interaction and food distribution systems. Food waste reduction strategies include improving food quality, implementing waste monitoring systems, enhancing staff competency, and optimizing menu planning according to patient preferences.